2022
DOI: 10.1590/s2175-97902022e20222
|View full text |Cite
|
Sign up to set email alerts
|

Association of cigarette and water-pipe smoking with increased visceral adiposity, glycemic intolerance and hematological derangement in Iraqi healthy smokers

Abstract: The present study aims to investigate the impacts of cigarette smoking (CS) and water-pipe smoking (WPS) on the visceral adiposity index (VAI), hematological characteristics, and glycemic tolerance in Iraqi healthy smokers. A total of 528 healthy males from different locations of Baghdad city were allocated to three groups; nonsmokers (176), cigarette smokers (178), and WP smokers (174). Baseline characteristics, anthropometric and hematological markers and were reported. Glycemic control was evaluated using t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 31 publications
3
0
0
Order By: Relevance
“…To put these results in context, we found a significant increase in Hb and RBCs just like many studies did, for instance, Nadia et al and Rawia Osman Ali studies [ 17 , 18 ] which were conducted in Sudan, a study even detailed that water pipes smokers especially demonstrated a significantly higher Hb value [ 19 ], which was in agreement with our findings. Another study [ 20 ] found that both Hb and RBC counts were significantly higher in WP smokers than in cigarette smokers.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…To put these results in context, we found a significant increase in Hb and RBCs just like many studies did, for instance, Nadia et al and Rawia Osman Ali studies [ 17 , 18 ] which were conducted in Sudan, a study even detailed that water pipes smokers especially demonstrated a significantly higher Hb value [ 19 ], which was in agreement with our findings. Another study [ 20 ] found that both Hb and RBC counts were significantly higher in WP smokers than in cigarette smokers.…”
Section: Discussionsupporting
confidence: 92%
“…Our results were generally consistent with the literature, the only contradiction was that our study found the HCT values to be significantly lower in cigarette smokers and no significant increase in WP smokers or both cigarette and WP smokers when compared to non-smokers, while most of those studies found a significant increase in HCT levels in smokers compared to non-smokers [ 17 – 22 ], some even demonstrated a higher increase in HCT levels among WP smokers compared to cigarette smokers [ 19 ]. More studies make it evident that there is some agreement on the effects of smoking on Hb and our data is building on this existing evidence [ 9 , 21 , 23 , 24 ].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation